1993
DOI: 10.1001/archsurg.1993.01420160023002
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Analogue Inhibits Intestinal Regeneration

Abstract: Somatostatin analogue octreotide inhibits intestinal absorption and motility but its effect on epithelial cell migration and proliferation remains unclear. Our aim was to determine the effect of octreotide on parameters of intestinal regeneration, including epidermal growth factor (EGF)-induced changes. Thirty rabbits had full-thickness ileal defects patched with cecal serosa surface. Group 1 were controls. Groups 2 and 3 received 100 micrograms and 1000 micrograms, respectively, of subcutaneous octreotide dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 27 publications
0
17
0
3
Order By: Relevance
“…Alternatively, somatostatin could influence the rate of mitosis and/or survival of neu-rons generated to replace damaged neurons after an injurious event. A growth-inhibitory action of somatostatin is well established for numerous tumors [for review, see Pollak and Schally, 1998] and for regeneration of several peripheral organs [e.g., Kokudo et al, 1992;Thompson et al, 1993;Zieleniewski and Zieleniewski, 1993;Bufalari et al, 1996]. Somatostatin appears to exert such a function through a cell cycle block due to G 1 arrest [Mascardo and Sherline, 1982] or through induction of apoptosis [Szende et al, 1989;Srikant, 1995].…”
Section: Role Of Somatostatin In Regenerationmentioning
confidence: 99%
“…Alternatively, somatostatin could influence the rate of mitosis and/or survival of neu-rons generated to replace damaged neurons after an injurious event. A growth-inhibitory action of somatostatin is well established for numerous tumors [for review, see Pollak and Schally, 1998] and for regeneration of several peripheral organs [e.g., Kokudo et al, 1992;Thompson et al, 1993;Zieleniewski and Zieleniewski, 1993;Bufalari et al, 1996]. Somatostatin appears to exert such a function through a cell cycle block due to G 1 arrest [Mascardo and Sherline, 1982] or through induction of apoptosis [Szende et al, 1989;Srikant, 1995].…”
Section: Role Of Somatostatin In Regenerationmentioning
confidence: 99%
“…EGF and basement membrane components also enhance migration. A number of inhibitory factors have also been identified, including the inhibitory polypeptide somatostatin, corticosteroids, and thiphenamil (Thompson, 1992; Thompson et al, 1988aThompson et al, , 1989Thompson et al, , 1993. These agents probably have pharmacologic or toxic effects rather than a physiologic role.…”
Section: Regulation Of Intestinalmentioning
confidence: 99%
“…Our previous studies demonstrated that proliferation is stimulated by growth factors, luminal contents, and associated intestinal resection and is also influenced by the crypt density around the injured area (Bragg and Thompson, 1986;Bragg et al, 1989;Saxena et al, 1997;Thompson, 1987Thompson, , 1990Thompson et al, 1985Thompson et al, , 1986Thompson et al, , 1987Thompson et al, , 1989Thompson et al, , 1990Thompson et al, , 1993. EGF, in particular, was found to be an important mitogenic factor although it is not clear if EGF is acting directly or via its stimulation of migration of epithelial cells.…”
Section: Regulation Of Intestinalmentioning
confidence: 99%
“…In Oncorhynchus mykiss, somatostatins inhibit growth by reducing hepatic GH sensitivity and by inhibiting growth hormone receptor (GHR) and IGF-I production (Hagemeister and Sheridan, 2008;Very and Sheridan, 2007). In mammal, somatostatins inhibit intestinal regeneration (Thompson et al, 1993) and cell proliferation and corticosterone secretion in the early stage of adrenal regeneration (Zieleniewski and Zieleniewski, 1993). These results suggest that PSSs may influence the secretion of gastroenteropancreatic hormones (Gahete et al, 2010).…”
Section: A B Cmentioning
confidence: 99%